Revocable identity-based proxy re-signature scheme in the standard model - Xiaodong YANG; Yutong LI; Jinli WANG; Tingchun MA; Caifen WANG (Tongxin xuebao)
User revocation is necessary to the practical application of identity-based proxy re-signature scheme.To solve the problem that the existing identity-based proxy re-signature schemes cannot provide revocation functionality,the notion of revocable identity-based proxy re-signature was introduced.Furthermore,the formal definition and security model of revocable identity-based proxy re-signature were presented.Based on proxy re-signature scheme and binary tree structure,a revocable identity-based proxy re-signature scheme was proposed.In the proposed,scheme,the user's signing key consists of two parts,a secret key and an update key.The secret key transmitted over the secure channel is fixed,but the update key broadcasted by the public channel is periodically changed.Only the user who has not been revoked can obtain the update key,and then randomize the secret key and update the key to generate the corresponding signature key of the current time period.In the standard model,the proposed scheme is proved to be existentially unforgeable against adaptive chosen-identity and chosen-message attacks.In addition,the proposed scheme has properties of bidirectionality and multi-use,and can resist signing key exposure attacks.The analysis results show that the proposed scheme can efficiently revoke the user and update the user’s key,and thus it has good scalability.